Analisa Peranan Sistem Informasi Manajemen Terhadap Bidang Pendidikan Dan Pajak - Aditia Aditia; Ines Heidiani Ikasari (Jurnal Riset Informatika dan Inovasi, 2023)
This study aims to analyze the role of management information systems in several industrial fields, one of which is education and tax. The method used in this study is a quantitative research method by collecting data through article surveys and article analysis. The results of this study are that the application of MIS in the Primary Tax Service Office in Manado increases efficiency in managing taxpayer tax reporting, even though there are obstacles in its application. At the Sukma Medan College of Management, the implementation of MIS in academic administration has increased efficiency in scheduling lectures and laboratories. Meanwhile, at SMP Negeri 9 Buru District, the application of MIS in education helps in providing better educational services and increasing the effectiveness of the learning process.